Hemodynamic Reactions during Removal of Brain Tumors with the Combined Use of Fentanyl and Alpha2-Adrenoagonist - M. V. Rumyantseva; L. M. Tsentsiper; A. N. Kondratiev (Вестник анестезиологии и реаниматологии)
Anesthesia including drugs that act on the opioid (fentanyl) and adrenergic (clonidine or dexmedetomidine) neuroregulatory systems, creates optimal conditions for performing brain surgery.The objective: to study the effect of combination of opioid analgesic fentanyl and alpha2-adrenoagonists on stability (reactivity) and appropriate functional activity of the circulatory system.Subjects and Methods. The study included 118 patients operated on for a brain tumor. Patients were divided into groups depending on the alpha2-adrenoagonist used, its dosage and position on the operating table.Results. In all groups, the required level of neurovegetative stabilization with stable hemodynamics was achieved at all stages of the operation. Conclusion. Studies have shown that a lower dose of dexmedetomidine versus clonidine was required to achieve a central sympatho-modulatory effect.